I'm having a bit of trouble with this one: If f(x) = -5x+6 and g(x) = 4x+5, find g(f(x)). The answer is somehow -20x+29. Shouldn't it be -20x+30?? Any help on how to solve this problem would be appreciated.
Follow Math Help Forum on Facebook and Google+
Originally Posted by softwareguy I'm having a bit of trouble with this one: If f(x) = -5x+6 and g(x) = 4x+5, find g(f(x)). The answer is somehow -20x+29. Shouldn't it be -20x+30?? Any help on how to solve this problem would be appreciated. g(f(x)) = g(-5x+6) = 4(-5x+6) +5 = .....
g(f(x)) says g(-5x+6) so you plug that into your x for g. =4(-5x+6)+5 6*4=24 + 5=29
The composition says, where ever you see "x" in g(x), to put the function f(x): $\displaystyle g(x) = 4x+5 \Rightarrow g(f(x)) = 4(-5x+6) + 5 \Rightarrow -20x+24+5 \Rightarrow -20x+29$
Originally Posted by Debsta g(f(x)) = g(-5x+6) = 4(-5x+6) +5 = ..... f(x) = -5x+6 g(x) = 4x+5 g(f(x)) = g(-5x+6) = 4(-5x+6) + 5 = -20x +24 +5 = -20x + 29
View Tag Cloud